Analysis of the Relationship between the Concept of Onrechtmatige Overheidsdaad and Maladministration Practices in Public Services in Indonesia - Pratiwi, Sukmananda Ahya; Arfah, Wahanani Leila; Sianturi, Stefanus (Veteran Law Review, 2024)
Effective public service provision is an essential responsibility of government institutions, and it is imperative to ensure that these services operate within the confines of applicable laws and regulations. Maladministration refers to the illegal or deviant practices carried out by government administrators or officials in the provision of public services. This study aims to classify maladministration as an act of illegality by the government, or onrechtmatige overheidsdaad, and examine the government's role in resolving these issues. Normative legal research methods were employed to achieve the study objectives. The findings of this research indicate that maladministration constitutes an unlawful act by state authorities/officials that causes harm to the community. Furthermore, Indonesia, as a state of law, has instituted legal and non-legal measures for resolving these issues.